(untitled) (International Journal of Biomedical Research, 2015)
Methylenetetrahydrofolate reductase (MTHFR) is a critical folate-metabolising enzyme and a polymorphism at position 677 (C677T), is associated with reduced enzyme activity. We investigated whether this functional polymorphism modulates the risk of developing Colorectal Cancer (CRC).